Continuous Renal Replacement Therapy for Severe Obstetric Sepsis - D. L. Shukevich; D. K. Peredelkin; Ye. V. Grigoryev; A. S. Razumov; Yu. A. Churlyaev; L. E. Shukevich (Общая реаниматология)
Objective: to improve the results of treatment for severe obstetric sepsis by pathogenetically founded continuous renal replacement therapies as extracorporeal homeostatic correction. Subjects and methods. Forty-two women with severe abdominal sepsis were divided into 3 groups: 1) 14 women with severe extragenital abdominal sepsis who received standard intensive care (a control group); 2) 12 women with severe obstetric sepsis who had standard intensive care (a study group); 3) 16 with severe obstetric sepsis who had the standard intensive care supplemented with continuous renal replacement therapy (an intervention group). Results. In Group 2, endogenous intoxication and multiple organ dysfunction were controlled later than in Group 1, mortality rates being 41.7 and 7.1%, respectively. Clinical laboratory differences were due to gestosis recorded in 100% of the patients with severe obstetric sepsis. When continuous renal replacement therapy was incorporated into the complex therapy of severe obstetric sepsis, there was a prompter regression of endogenous intoxication and multiple organ dysfunction, mortality was decreased by an average of 35% as compared with that during standard therapy. Conclusion. The inclusion of continuous renal replacement therapy into the complex treatment program for severe obstetric sepsis made it possible to reduce control time _ for endogenous intoxication and multiple organ dysfunction and to decrease mortality by an average of 35% as compared with that during standard intensive care. Key words: obstetric sepsis, abdominal sepsis, gestosis, endogenous intoxication, multiple organ dysfunction, renal replacement therapy.